Analysis of Errors in Using Indonesian on Banners in the Selebar District of Bengkulu City - Yesi Arinti; Gulandom Hamraqulova Sodiq Qizi; Nurhaswanee Boto (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: The aim of this study is to identify and analyze errors in spelling and discourse in the use of the Indonesian language on banners in Kecamatan Selebar, Kota Bengkulu, to improve the clarity and effectiveness of public communication. Methodology: The type of research used in this research is qualitative. Qualitative research is descriptive research and tends to use analysis with an inductive approach. The subjects in this research are banners in the Selebar District area of Bengkulu City. The data collection techniques that the author used in conducting this research were interview, observation and documentation techniques. Testing the validity of the data in this research uses triangulation techniques. The method of data analysis that the author carried out in this research was following the Miles and Huberman model. Main Findings: The research results show that spelling and punctuation errors, such as the use of hyphens, abbreviations, as well as periods and slashes that do not comply with the General Guidelines for Indonesian Spelling (PUEBI), often occur and can hinder understanding of the message conveyed. Novelty/Originality of this study: The novelty of this research lies in the focus of analyzing spelling errors and discourse in the use of Indonesian on banners in Selebar District, Bengkulu City, which is a non-academic media and is directly related to the wider community.